Minor compounds from virgin olive oil attenuate LPS‐induced inflammation via visfatin‐related gene modulation on primary human monocytes. Issue 8 (3rd June 2019) - Martin, Maria E.; Millan‐Linares, Maria C.; Naranjo, Maria C.; Toscano, Rocío; Abia, Rocio; Muriana, Francisco J. G.; Bermudez, Beatriz; Montserrat‐de la Paz, Sergio
Abstract: We have analyzed the effects of minor compounds found in the unsaponifiable fraction (UF) and in the phenolic fraction (PF) of virgin olive oil (VOO) on LPS‐induced inflammatory response via visfatin modulation in human monocytes. For this purpose, monocytes were incubated with UF and PF at different concentrations and the pro‐inflammatory stimulus LPS for 24 hr; squalene (SQ) and hydroxytyrosol (HTyr), the main components in UF and PF, respectively, were also used. The relative expression of both pro‐inflammatory and anti‐inflammatory genes, as well as other genes related to the NAD+‐biosynthetic pathway was evaluated by RT‐qPCR; and the secretion of some of these markers was assessed by ELISA procedures. We found that UF, SQ, PF, and HTyr prevented from LPS‐induced dysfunctional gene expression and secretion via visfatin‐related gene modulation in human monocytes. These findings unveil a potential beneficial role for minor compounds of VOO in the prevention of inflammatory‐disorders. Practical application: In this project, potential health benefits of VOO micronutrients (unsaponifiable and phenolic compounds) were confirmed through anti‐inflammatory assays. Our results reveal new interesting researching goals concerning nutrition by considering the role of bioactive VOO compounds in the prevention and progress of diseases related to inflammation.